PENGARUH MINAT BELAJAR DAN BIMBINGAN BELAJAR BAHASA ARAB AL-MUFLIHIN TERHADAP HASIL BELAJAR SISWA DI KABUPATEN MAJENE (Universitas Negeri Semarang, 2022)
The purpose of this study was to determine the effect of interest in learning and Arabic tutoring Al-Muflihin on student learning outcomes in Majene Regency. This type of research is quantitative and the research design uses ex post facto research methods using multiple linear regression analysis models. The subjects in this study were 20 students, who were taken using a saturated sampling technique. From the research results, there is a positive and significant influence between learning interest on student learning outcomes, with regression equation analysis Y = 21.319 + 0.572X. The value of the coefficient of determination is 50.8% and the remaining 49.2% is influenced by other factors. There is a positive and significant influence between tutoring on student learning outcomes, with regression equation analysis Y = 26.395 + 0.515X. The coefficient of determination is 85% and the remaining 15% is influenced by other factors. There is a positive and significant influence between learning interest and tutoring on student learning outcomes, with regression equation analysis Y = 2.419 + 0.295X1 + 0.421X2. The value of the coefficient of determination X1 and X2 is 95.7% and the remaining 4.3% is influenced by other factors not included in this study. So the conclusion is that there is a significant relationship between learning interest and Al-Muflihin Arabic tutoring on student learning outcomes in Majene Regency.